Day hospital treatment for people with severe mental illness according to users' perspectives: what helps and what hinders recovery?. (2nd January 2018) - Agrest, Martín; Barruti, Silvina; Gabriel, Raquel; Zalazar, Virginia; Wikinski, Silvia; Ardila-Gómez, Sara
Abstract: Background : Scarce information is available about how users experience treatment at mental health day hospitals, particularly in South America. Aims : To explore users' perspectives about elements of day hospital treatment that facilitate or hinder the recovery process in a mental health facility in Buenos Aires, Argentina. Methods : Semi-structured individual interviews ( n  = 8) and focus groups ( n  = 4) were carried out with a convenience sample of users of a mental health day hospital program based on a formulation, testing and redevelopment of propositions approach. Results were analyzed through grounded theory techniques. Results : Categories indicating recovery were: starting to do things, being able to see themselves from a new perspective, mood improvement and changes in interpersonal relationships. Aspects facilitating recovery were: activities organized by the facility, the group approach, the care provided by facility workers and the physical environment. Hindering aspects were: heterogeneity of users in terms of age, severity, diagnosis and being underestimated by staff. Conclusions : Being active again was considered to be the main recovery indicator in this cultural context and participating in activities led by skilled facilitators was the most beneficial factor of the program according to the users.